Xonotlite-, Pectolite- and Natrolite-Bearing Fracture Veins in volcanic Rocks from Nûgssuaq, West Greenland. - Karup-Møller, S. (Meddelelser om Grønland, 1969)
Fracture veins containing calc-silicate and zeolite minerals are developed in tuft, pillow lava and olivine basalts from the West Greenland basaltic province. The minerals in the veins can be grouped into three distinct suites, each of which is characterized by one dominant mineral. The minerals are xonotlite, pectolite and natrolite. The suites are developed at different horizons in the volcanic sequence, the lowest being the xonotlite suite, followed by the pectolite suite and uppermost, the natrolite suite. The mineral suites are believed to have been formed from hydrothermal solutions at around 300°C and at pressures less than 300 bars. These solutions may have been of magmatic origin, possibly mixed with percolating sea water. It is thought that the suites crystallized in systems at equilibrium under temperature conditions corresponding to the upper zeolite and lower greenschist metamorphic facies.